Electrochemically mediated precipitation of phosphate minerals for phosphorus removal and recovery: Progress and perspective. (1st February 2022) - Wang, Yicheng; Kuntke, Philipp; Saakes, Michel; van der Weijden, Renata D.; Buisman, Cees J.N.; Lei, Yang
Highlights: Electrochemical mediated precipitation (EMP) of phosphate minerals were reviewed. Mechanism and influences of EMP towards P recovery were discussed. EMP has the unique advantage of recovering both ortho and non-ortho P. Challenges and limitations of EMP in P recovery were identified. Future research should focus on upscaling under environment relevant conditions. Abstract: Phosphorus (P) is an essential element for the growth and reproduction of organisms. Unfortunately, the natural P cycle has been broken by the overexploitation of P ores and the associated discharge of P into water bodies, which may trigger the eutrophication of water bodies in the short term and possible P shortage soon. Consequently, technologies emerged to recover P from wastewater to mitigate pollution and exploit secondary P resources. Electrochemically induced phosphate precipitation has the merit of achieving P recovery without dosing additional chemicals via creating a localized high pH environment near the cathode. We critically reviewed the development of electrochemically induced precipitation systems toward P removal and recovery over the past ten years. We summarized and discussed the effects of pH, current density, electrode configuration, and water matrix on the performance of electrochemical systems. Next to ortho P, we identified the potential and illustrated the mechanism of electrochemical P removal and recovery from non-ortho P compounds by combined anodic or anode-mediated oxidation and cathodic reduction (precipitation). Furthermore, we assessed the economic feasibility of electrochemical methods and concluded that they are more suitable for treating acidic P-rich waste streams. Despite promising potentials and significant progress in recent years, the application of electrochemical systems toward P recovery at a larger scale requires further research and development. Future work should focus on evaluating the system's performance under long-term operation, developing an automatic process for harvesting P deposits, and performing a detailed economic and life-cycle assessment. Graphical abstract: Image, graphical abstract